2019
DOI: 10.1039/c9ta01559k
|View full text |Cite
|
Sign up to set email alerts
|

A metal–organic framework converted catalyst that boosts photo-electrochemical water splitting

Abstract: We show that a MOF-converted compound can act as highly active co-catalyst in a water splitting photo-electrochemical cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 52 publications
(53 reference statements)
1
47
0
Order By: Relevance
“…However, the rapid recombination of electrons generated from MOFs and the fast oxidization by charge transfer are the main problems for PEC systems. Hence, a recent study has demonstrated that a great enhancement on the performance of a water-splitting PEC could be achieved by using a surface-modified ZIF-67 MOF-derived semiconductor, which contains highly porous cobalt oxide (CoO x ) and BiVO 4 co-catalysts, as the photoanode to accelerate the kinetics of water oxidation rather than serving as a surface passivation layer [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the rapid recombination of electrons generated from MOFs and the fast oxidization by charge transfer are the main problems for PEC systems. Hence, a recent study has demonstrated that a great enhancement on the performance of a water-splitting PEC could be achieved by using a surface-modified ZIF-67 MOF-derived semiconductor, which contains highly porous cobalt oxide (CoO x ) and BiVO 4 co-catalysts, as the photoanode to accelerate the kinetics of water oxidation rather than serving as a surface passivation layer [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardenas‐Morcoso et al prepared modified BiVO 4 ‐CoOx photoelectrocatalyst by synthesizing ZIF‐67 MOF on top of BiVO 4 . After calcination, deposited MOF was converted to CoO x co‐catalysts that showed significant boosts in PEC water‐splitting 92 . Xu et al prepared a thin film coating of Co‐MOF derived from ZIF‐67.…”
Section: Synthesis Methods For Mof‐based Catalysts For Water‐splittingmentioning
confidence: 99%
“…PEC characterization of modified photoanodes revealed almost four times higher photocurrents and enhanced catalytic performance compared to bare BiVO 4 photoanode (Shown in Figure 16). 92 …”
Section: Recent Advances In Water‐splitting By Mof‐based Catalystsmentioning
confidence: 99%
See 2 more Smart Citations